Ventral cochlear nucleus bushy cells encode hyperacusis in guinea pigs - Martel, David T. (Sci Rep, 2020)
Psychophysical studies characterize hyperacusis as increased loudness growth over a wide-frequency range, decreased tolerance to loud sounds and reduced behavioral reaction time latencies to high-intensity sounds. While commonly associated with hearing loss, hyperacusis can also occur without hearing loss, implicating the central nervous system in the generation of hyperacusis. Previous studies suggest that ventral cochlear nucleus bushy cells may be putative neural contributors to hyperacusis. Compared to other ventral cochlear nucleus output neurons, bushy cells show high firing rates as well as lower and less variable first-spike latencies at suprathreshold intensities. Following cochlear damage, bushy cells show increased spontaneous firing rates across a wide-frequency range, suggesting that they might also show increased sound-evoked responses and reduced latencies to higher-intensity sounds. However, no studies have examined bushy cells in relationship to hyperacusis. Herein, we test the hypothesis that bushy cells may contribute to the neural basis of hyperacusis by employing noise-overexposure and single-unit electrophysiology. We find that bushy cells exhibit hyperacusis-like neural firing patterns, which are comprised of enhanced sound-driven firing rates, reduced first-spike latencies and wideband increases in excitability.